Penguatan Branding dan Pemasaran Digital pada UMKM Warung “Mbak Raisha” di Pantai Karang Jahe, Kabupaten Rembang - Muhammad Kholilur Rohman; Aelia Rara Dianti; Siti Utami; Dian Anita Sari (Pusat Riset dan Inovasi Nasional, 2025)
Karang Jahe Beach is one of the leading tourism destinations located in Rembang Regency. This area provides a great opportunity for Micro, Small, and Medium Enterprises (MSMEs) to develop and reach a wider market. One of the MSMEs in this area is Warung